Factors Influencing Stock Investment Decision among Individual Investors of Chitwan, Nepal - Wagle, Sudip (Journal of Business and Management, 2024)
Background: Stock investment is one of the most important growth indicators for the economy because it makes a great contribution to the nation’s growth and brings significant returns to investors. However, the behavioral factors of individuals are producing confusion for investors.Objectives: The objective of this study is to identify the main factors influencing individual investors’ decisions in stock investments.Methods: This study utilizes a structured questionnaire survey conducted with 385 trade management system (TMS) account holders and employs a descriptive and causal-comparative research design. Analytical techniques such as percentage, mean, standard deviation, correlation, and regression analysis were applied.Results: The study discovered a significant positive impact among all the influencing variables and stock investment decisions. However, the study results exposed a greater significance of accounting information and stock investment decisions.Conclusion: The findings concluded that accounting information and investment decision were highly influential dimensions of stock investment, followed by optimism, advocate recommendation, herd behavior and overconfidence